A study of the concept and practice of German “family-friendly companies” and some insights for China - Xiaoshan Ni; Ute Klammer (Humanities & Social Sciences Communications)
Abstract Since the 1990s, the German federal government has introduced various family-friendly policies aimed at enhancing work-life balance and fostering economic growth. In contrast, China’s initiatives to promote family-friendly workplaces are relatively recent, with major efforts beginning in January 2022 under the leadership of the Shanghai Women’s Federation. Given China’s aging population, the establishment of such companies is increasingly imperative, although policy development and research in this area remain nascent. This paper begins by clarifying key concepts related to family-friendly companies through a literature review. Subsequently, it introduces a theoretical framework of multiple family equilibria to explore the underlying logic of implementing family-friendly practices. A life cycle-oriented categorization scheme for areas of possible action is proposed to guide the empirical study. To examine the perspective of an audit and certification body, we investigate German companies certified as “audit berufundfamilie® family-friendly employers” between 1999 and 2022, summarizing their characteristics and performance in implementing family-friendly policies. Finally, following an in-depth discussion of the factors influencing the effectiveness of family-friendly corporate policies and the applicability of the German model within the Chinese context across societal, corporate, and employee dimensions, this paper offers several constructive suggestions for establishing and fostering family-friendly companies in China, drawing on the experiences of Germany.